Association of dysmenorrhea with stress among female students at Universal College of Medical Sciences, Bhairahawa - Gurung, Preetu; Jha, Jay Prakash; Joshi, Bishal (Journal of Karnali Academy of Health Sciences, 2024)
Background: Dysmenorrhea, the cramping pain experienced by women during menstruation, can significantly impact their daily lives and academic performance. Mental stress is a potential trigger for dysmenorrhea, but their association remains to be precisely determined. This study aims to explore the prevalence of dysmenorrhea among undergraduate female students at Universal College of Medical Sciences and investigate its association with perceived stress.Methods: A descriptive cross-sectional study was conducted among undergraduate female students at Universal College of Medical Sciences, Bhairahawa. Participants were selected using a simple random sampling method. A structured questionnaire, including anthropometric data, menstrual history, and the Perceived Stress Scale (PSS), were used for data collection. PSS scores were used to categorize stress levels as low, moderate, or high.Results: Total 196 female students participated in the study. Dysmenorrhea was present in 80.1% of the participants, with 34.7% seeking treatment for the condition. Additionally, 29.6% of the students reported moderate to severe premenstrual symptoms. Most students (81.6%) had a moderate level of perceived stress. Statistical analysis revealed a significant association between dysmenorrhea and level of perceived stress (p < 0.001).Conclusion: The study findings highlight a considerable prevalence of dysmenorrhea among female students at Universal College. The association between dysmenorrhea and perceived stress underscores the importance of addressing the psychosocial well-being of these students. Implementing supportive measures, such as mental health support and stress management programs, can create a more conducive environment for students to manage dysmenorrhea and its impact on their academic performance.